IMPLEMENTATION OF SPORTS NATIONAL POLICY ON SPORT LEARNERS IN NORTH SUMATRA - Nimrot Manalu (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
The purpose of this research is to get information about the implementation of national sports policy towards student sport in North Sumatra. This research is a qualitative research. The focus of this research is to explore the real situation occurring in the forefront of the national sports and sports policy of North Sumatra students collected by interview method. The result is that there is no harmony between the sports policy and the reality society of sports in North Sumatra. This research gave birth to recommendations such as the need to optimize the socialization of Law No. 3 of 2005, Regulation of Government no. 18,17,18 among physical education teachers and trainers of Sports Students in North Sumatra are communicative, chain and quality. Need to be socialized National sports programs or projects such as the need for guidance or guidance for students' recreational sports, it is necessary to establish guidelines for the establishment of student achievement sports, to optimize the existence of Board of Trustees of Student Sport throughout Indonesia, it is necessary to realize the procurement of sports science and technology in schools that build sport achievement in North Sumatra, it is necessary to realize the establishment of the Student Training Center Training Center at the district / city level, it is necessary to realize the presence of special trainers of sports with the status of civil servants in school schools, and the need to realize sports championships or students' sports week at each level of city districts periodically and continuously. Keywords: National Policy Implementation of Sports, Sports Student